Rancangan sistem catu daya listrik pada bandara sultan bantilan tolitoli - Vovi Azepi G. Soeka Raja; Edy Kurniawan; Suse Lamtiar S (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Airports are critical facilities that require a reliable electrical power supply system to ensure safety and continuity of flight operations. The construction of a new terminal at Sultan Bantilan Tolitoli Airport has significantly increased electrical load demand; however, this development was not accompanied by an increase in secondary power supply capacity. This condition potentially reduces the reliability of the electrical system, particularly during disturbances in the main power source.This study aims to analyze the existing electrical power supply system, evaluate the adequacy of power capacity relative to current load demands, and design a more reliable power distribution system. The research employs a descriptive–explanatory method with a case study approach. The research stages include electrical load data collection, analysis of primary and secondary power supply capacity, separation of essential and non-essential loads, and system modeling and simulation using ETAP software.The results indicate that the existing secondary power supply or generator set capacity are insufficient to support the airport’s total electrical load after terminal expansion. Redesigning the distribution system by prioritizing essential loads and optimizing generator operation improves the reliability of power supply to critical loads. ETAP simulation results show that the proposed system meets acceptable technical limits for power flow and voltage profiles. Therefore, the proposed power supply system design is considered feasible to enhance the reliability and continuity of electrical power supply at Sultan Bantilan Tolitoli Airport